(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The paper analyses the first book of Eustahia Arsić, the first Serbian woman of letters of the modern age. Even though some parts of Sovjet maternij (1814) are addressed exclusively to women readers, her approach is universal and more emancipatory than feminist. The book has a recognizable hybrid structure, well known since Dositej Obradović’s autobiography and maintained during the 19th century. Essayistic discourse about the Enlightenment subjects of interest (education and character building in the terms of ideas deriving from Rousseau’s philosophy) is combined with four poems. These poems appear as the standard examples of sentimentalism in Serbian poetry, but they are also early examples of texts formulating the motive of the Supreme Creator eternally present in the course of “life” of nature and universe. In that way, her work appears as the anticipation of the distinctive feature of the Serbian 19th century poetry.